Know your risks : preventing disasters! - Talbot, Kathryn (My University, 2014)
This presentation introduces KCHERN, Kansas Cultural Heritage Emergency Response Network, followed by a “Disaster Planning 101” approach to risk assessment. Presenter: Kathryn Talbot, Preservation Coordinator, Hale Library, Kansas State University.
Keywords: Museums; Collection disasters; Emergency management; Emergency management--Handbooks, manuals, etc.; Museums--Conservation and restoration--Handbooks, manuals, etc.